Rancang Bangun Aplikasi Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa pada Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Manyar Surabaya. - yuyun Eka Wahyutri; Sulistio Wati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2015)
Abstract: application analysis of the influence of service quality on student satisfaction aims to help obtain information on the impact of service quality student satisfaction. With this application, it is expected LP3I Manyar Surabaya can find any information and factors that influence student satisfaction, so LP3I can improve the quality of services and evaluating the student satisfaction LP3I Manyar Surabaya. However, LP3I Manyar Surabaya have difficulty in data processing, data analysis. so the impact on the error in reporting the results of student satisfaction measurement. To resolve this problem, made an application ranging from data processing to determine the value of the variable. The results of the process were analyzed using linear regression method can be shown that the quality palayanan affect student satisfaction. Keywords : Application of Service Quality Analysis,Multiple Linier Regression